Donor-Derived CD7 Chimeric Antigen Receptor T Cells for T-Cell Acute Lymphoblastic Leukemia: First-in-Human, Phase I Trial. Issue 30 (20th October 2021) - Pan, Jing; Tan, Yue; Wang, Guoling; Deng, Biping; Ling, Zhuojun; Song, Weiliang; Seery, Samuel; Zhang, Yanlei; Peng, Shuixiu; Xu, Jinlong; Duan, Jiajia; Wang, Zelin; et al.
Abstract : PURPOSE: Patients with relapsed or refractory T-cell acute lymphoblastic leukemia (r/r T-ALL) have few options and poor prognosis. The aim was to assess donor-derived anti-CD7 chimeric antigen receptor (CAR) T-cell safety and efficacy in patients with r/r T-ALL. METHODS: In this single-center, phase I trial, we administered anti-CD7 CAR T cells, manufactured from either previous stem-cell transplantation donors or new donors, to patients with r/r T-ALL, in single infusions at doses of 5 × 10 5 or 1 × 10 6 (±30%) cells per kilogram of body weight. The primary end point was safety with efficacy secondary. RESULTS: Twenty participants received infusions. Adverse events including cytokine release syndrome grade 1-2 occurred in 90% (n = 18) and grade 3-4 in 10% (n = 2), cytopenia grade 3-4 in 100% (n = 20), neurotoxicity grade 1-2 in 15% (n = 3), graft-versus-host disease grade 1-2 in 60% (n = 12), and viral activation grade 1-2 in 20% (n = 4). All adverse events were reversible, except in one patient who died through pulmonary hemorrhage related to fungal pneumonia, which occurred at 5.5 months, postinfusion. Ninety percent (n = 18) achieved complete remission with seven patients proceeding to stem-cell transplantation. At a median follow-up of 6.3 months (range, 4.0-9.2), 15 remained in remission. CAR T cells were still detectable in five of five patients assessed in month 6, postinfusion. Although patients' CD7-positive normal T cells were depleted, CD7-negative T cells expanded and likely alleviated treatment-related T-cell immunodeficiency. CONCLUSION: Among 20 patients with r/r T-ALL enrolled in this trial, donor-derived CD7 CAR T cells exhibited efficient expansion and achieved a high complete remission rate with manageable safety profile. A multicenter, phase II trial of donor-derived CD7 CAR T cells is in progress (NCT04689659 ). Abstract :